Eksplorasi Teknik Crochet pada Kerajinan Eceng Gondok - Kiera Ashley; Hairunnas; Hairunnas (Penerbit Itenas, 2025)
This study aims to explore the potential of water hyacinth fibers as an alternative material in crochet techniques for crafting handmade products, particularly storage containers. Traditionally, water hyacinth has been utilized through weaving techniques, although its characteristics are also suitable for methods such as crocheting. This research adopts a Research Through Design approach, involving experiments in texture restoration, fiber processing, strand joining, moisture and motif effects, 3D shaping, and coloring. The results show that water hyacinth stems soaked in regular water for 10 minutes, then cut into 0.5 cm strips and crocheted while damp, produce the best-quality yarn. Despite limitations in forming sharp-edged shapes like cubes and hexagons, the crocheted structures remain sturdy and functional as storage containers. This innovation offers a more diverse processing technique for water hyacinth, enhancing its aesthetic value and contributing to eco-friendly waste reduction in aquatic areas.